PEDAGOGICAL TEACHER COMPETENCE: USING OBSERVATION TECHNIQUES TO UNDERSTAND CHARACTERISTICS OF STUDENTS IN ELEMENTARY SCHOOLS - Teguh Prasetyo; Yufiarti Yufiarti; Rasmitadila Rasmitadila (Pedagogi, 2022)
Teacher pedagogical competence is an essential component of primary school teachers. Teacher pedagogy can assist in the management of student learning and demonstrate professionalism in teaching in the classroom. This study aims to explore how teachers apply pedagogic competence to understand the characteristics of elementary school students. The research design uses a qualitative approach with a descriptive analysis of the teacher's pedagogic competence in understanding student characteristics in elementary schools. The Collecting data and analysis using structured interviews with ten primary respondents of the study. The results of the study show how teachers use direct observation techniques on the characteristics of elementary school students. Direct observation is the primary method in observing the characteristics of students, which include aspects of physical, intellectual, socio-emotional, socio-cultural, moral and spiritual, and socio-cultural background of students. The most dominant observation aspect in observing students is the socio-emotional and intellectual characteristics during learning in elementary school. This study implies that understanding student characteristics is more directed at observing aspects of whether students tend to have special needs or not and whether students experience problems with intellectual abilities.